Potensi Aktivitas Antagonistik Streptomyces dari Rhizosfer Pohon Pule (Alstonia scholaris) sebagai Biokontrol - Isrianto, Pramita Laksitarahmi; Wilujeng, Sukian; Marmi, Marmi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Pule plant (Alstonia scholaris) is one of the plants that is often chosen for greening purposes and can be used as a medicinal plant. The ability of Pule plant interaction with microbes is shown from its potential as a source of beneficial microbes, both from the phyllosphere, rhizosphere, and endophytes. The tree rhizosphere microbial ecosystem plays an important role in maintaining tree health and has the potential to produce microorganisms with biocontrol activities. This study aims to evaluate the antagonistic activity of Streptomyces sp isolated from the rhizosphere of Pule trees (Alstonia scholaris) on the ability to inhibit pathogenic bacteria. The research method used disc antagonist test to determine the effectiveness of Streptomyces sp. in inhibiting the growth of pathogenic bacteria, macroscopic and microscopic characterization observations to identify isolates, as well as KOH test and catalase test. The test samples were Streptomyces isolates against Bacillus sp., Fusarium sp., and Aspergillus sp. and the data were analyzed descriptively. The results showed that the isolate Streptomyces sp. has the ability to inhibit the growth of Bacillus sp. and Fusarium sp. In biochemical tests revealed that the isolate is a gram-positive bacterium, based on the results of the KOH test showed that Streptomyces sp. is not slimy (+), while the catalase test produced negative (-) showed no bubbles, meaning Streptomyces sp. does not inhibit the growth of Bacillus sp. and Aspergillus sp.